Analisis Kalor Pada Alat Pengolah Sampah Plastik Dengan Metode Pyrolisis Dengan Perbandingan Tipe Sampah Plastik - Ahmad yunus nasution (Fakultas Teknik UM Pontianak, 2020)
In this modern era, the use of plastic is very much in the community, this alone makes the accumulation of plastic waste. And the nature of plastic waste has properties that are difficult to decompose and even need hundreds of years, this is also what makes the accumulation of plastic waste. Of the menabahnya amount of plastic such as plastic materials that can only be used and thrown for example are mineral water bottles, plastic bags or plastic food wrappers and This type of sterofoam waste is the most widely used and most piles of garbage collection.In my analysis process the plastic that will be processed using the pyrolysis method is rubbish whose category is plastic waste made from vinyl chloride, polyethylene, acrylic, silicone, urethane , which we can find most of its use as food packaging or household plastic appliances. Comparison of the first plastic garbage type of type 1: Polyethylene Terephthalate (PET or PETE or Polyester) and type 2: High Density Polyethylene (HDPE) , with the amount of plastic waste ratio of 1: 1. Comparison to two types of 1: Polyethylene Terephthalate (PET or PETE or Polyester) and type 4: Low Density Polyethylene (LDPE) , with a ratio of 1: 1 plastic waste. Comparison of all three types of 1 : Polyethylene Terephthalate (PET or PETE or Polyester) and type 6: Polystyrene (PS) , the amount of plastic waste ratio of 1: 1.Results from this study obtain data Data obtained from PET & HDPE experiments obtained oil and heat obtained from experiments 1 to 5. On The first experiment oil obtained was 0.15 Liters and Heat for evaporation of material was 2829.78 kJ. On The Second experiment oils obtained were 0.74 Liters and Heat for the evaporation of material 2829.78 kJ . On The third experiment oil obtained was 0.74 liters and heat for the evaporation of material 2829.78 kJ. On The Fourth experiment oils obtained were 0.74 Liters and Heat for the evaporation of material 2829.78 kJ . On The Fifth experiment oils obtained were 0.74 Liters and Heat for evaporation of the material 2829.78 Kj .Data obtained from PET & LDPE experiments obtained oil and heat obtained from experiments 1 to 5. On The First experiment oil obtained was 0.47 Liters and Heat for evaporation of 4119.3 kJ material . On The Second experiment oils obtained were 0.51 Liters and Heat for evaporation of 4334.22 kJ material . On The third experiment oil obtained was 0.36 liters and heat for evaporation of material 4226.76 kJ . On The Fourth experiment oils obtained were 0.44 Liters and Heat for evaporation of 5014.8 kJ material . On The Fifth experiment oils obtained were 0.5 Liters and Heat for the evaporation of ingredients 4477.5 Kj.